2021
DOI: 10.1093/function/zqab029
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the MuRF1 Skeletal Muscle Ubiquitylome Through Quantitative Proteomics

Abstract: MuRF1 (TRIM63) is a muscle-specific E3 ubiquitin ligase and component of the ubiquitin proteasome system. MuRF1 is transcriptionally upregulated under conditions that cause muscle loss, in both rodents and humans, and is a recognized marker of muscle atrophy. In this study, we used in vivo electroporation to determine if MuRF1 overexpression alone can cause muscle atrophy and, in combination with ubiquitin proteomics, identify the endogenous MuRF1 substrates in skeletal muscle. Overexpression of MuRF1 in adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 71 publications
1
44
0
Order By: Relevance
“…Two of the most important E3 ubiquitin ligases with respect to UPS are Muscle RING-finger protein-1 (MuRF-1) and atrophy gene-1/muscle atrophy f-box (Atrogin-1/MAFbx). These proteins are responsible for the degradation of several myofibrillar, sarcomeric, and related regulatory proteins [8,9]. The UPS is commonly upregulated in many other wasting conditions and is heavily influenced by the forkhead box class O (FOXO) transcription factor family [10].…”
Section: Protein Degradationmentioning
confidence: 99%
“…Two of the most important E3 ubiquitin ligases with respect to UPS are Muscle RING-finger protein-1 (MuRF-1) and atrophy gene-1/muscle atrophy f-box (Atrogin-1/MAFbx). These proteins are responsible for the degradation of several myofibrillar, sarcomeric, and related regulatory proteins [8,9]. The UPS is commonly upregulated in many other wasting conditions and is heavily influenced by the forkhead box class O (FOXO) transcription factor family [10].…”
Section: Protein Degradationmentioning
confidence: 99%
“…HUWE1, see Table II). Desmin was recently reported to be ubiquitinated by the ubiquitin ligase MURF1 in normal mouse muscles overexpressing Murf1 , though this ubiquitination of desmin did not lead to degradation (Baehr et al, 2021). We could not precipitate MURF1 with ATAD1 from denervated muscle extracts, and it remains to be determined if MURF1 acts on desmin in vivo during atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Baehr et al (66) demonstrated that overexpression of MuRF1, but not MAFbx, is sufficient to induce muscle atrophy in mice. In an attempt to understand how MuRF1 regulates myofibrillar protein degradation, Baehr et al (66) identified MuRF1 overexpression-dependent ubiquitylation sites on 56 proteins.…”
Section: E3 Ligases In Skeletal Musclementioning
confidence: 99%
“…More recently, Baehr et al (66) demonstrated that overexpression of MuRF1, but not MAFbx, is sufficient to induce muscle atrophy in mice. In an attempt to understand how MuRF1 regulates myofibrillar protein degradation, Baehr et al (66) identified MuRF1 overexpression-dependent ubiquitylation sites on 56 proteins. Surprisingly, their validation showed that the majority of these MuRF1 substrates do not undergo degradation, which is in contrast to Clarke et al's findings (67) that MuRF1 physically associates with and degrades slow and fast myosin heavy chains under Figure 2.…”
Section: E3 Ligases In Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation